Expanding access to COVID-19 testing, vaccination and treatment at a free clinic for uninsured Spanish-speaking adults in Providence, RI - Katherine Barry; Johanna A. Suskin; Julia Testa; Morgan Leonard; Anne S. De Groot (Taylor & Francis Group, 2022)
The COVID-19 pandemic disproportionately impacted uninsured and minority populations, contributing to and reinforcing long-lasting health inequities. Clínica Esperanza/Hope Clinic (CEHC), a free clinic serving uninsured individuals, is one 'safety-net' clinic that improved access to COVID-19 testing and vaccinations for an at-risk population during the pandemic. A retrospective review was performed to quantify COVID-19 testing and vaccination rates for clinic participants, which were compared to rates in the general population. 51.7% of patients seeking COVID-related care at CEHC were uninsured, compared to 8% in Providence and 4.8% in Rhode Island. CEHC performed 5,623 COVID-19 tests for 4,498 unique individuals, a total of 15,783 vaccines were administered, and 10 to 20% of COVID-care participants reported food insecurity during the study period. The prevalence of COVID-19 in the uninsured population and the high demand for vaccines highlight the important role that free clinics can play in the pandemic setting.